Potential of Bioactive Peptides From Blanak Fish (Moolgarda Seheli) as Multitarget Therapy for Non-small Cell Lung Cancer: A Cancer-informatics Study - Ramadhana, Reza; Maulana, Rafi; Al Habsy, Muhammab Nandito (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Non-Small Cell Lung Cancer (NSCLC) is the most common type of lung cancer with a high mortality rate and resistance to conventional therapy. Moolgarda seheli is known to produce bioactive compounds, but its potential against NSCLC still needs to be explored. This study aims to evaluate the pharmacokinetic profile, pharmacodynamics, and potential of M. seheli peptides as a multitarget agent for NSCLC through an in silico approach. Twelve M.seheli peptides were modeled using UCSF Chimera. Pharmacokinetic and pharmacodynamic predictions were performed using SwissADME, ProTox-3.0, and AllerTop. Membrane permeability was evaluated using PerMM. Target protein structures were obtained from PDBJ. Molecular docking was performed with MOE, then validated through molecular dynamics simulation (MD) using YASARA. Plasmid construction was performed in silico using ApE v2.0.36. Pharmacokinetic and pharmacodynamic profiles indicate the AVMAPIVA peptide has favorable distribution, metabolism, and excretion, as well as non-toxic and non-allergenic properties. The AVMAPIVA peptide exhibits strong affinity for CDK4 (-10.75 kcal/mol), BRAF (-11.60 kcal/mol), AKT1 (-10.79 kcal/mol), VEGFR2 (-10.73 kcal/mol), and EGFR (-10.47 kcal/mol). PerMM results indicate good membrane penetration ability. MD simulations confirm the stability of the complex. The results of the study indicate that the AVMAPIVA peptide is non-toxic, non-allergenic, stable in biological environments, and capable of penetrating cell membranes and inhibiting proliferation, migration, and angiogenesis in NSCLC. peptide from M. seheli has potential as a multitarget therapy for NSCLC with a good druglikeness profile. In vitro and in vivo experimental studies are needed for further validation of efficacy and safety.   Keywords: Moolgarda seheli, Multitarget, NSCLC, Peptide-based therapy, Bioinformatics.